1991
DOI: 10.1016/0168-0102(91)90075-a
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine D2-receptor mRNA level in rat striatum after chronic haloperidol treatment

Abstract: Chronic treatment with haloperidol, a D2-receptor antagonist and a neuroleptic, increases the number of D2-receptors in rat striatum. However, there have been inconsistent reports on the D2-receptor mRNA level, one showing the increase in the mRNA level and another detecting no changes. Furthermore, they did not distinguish the two isoforms of D2-receptor, D2A and D2B. In the present work, both D2- and DeA-receptor mRNA levels in rat striatum were estimated after chronic administration of haloperidol. There wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…The concentration of [ 3 H]-spiperone used in this study is approximately 7 times the K d for the D 2 receptor and, thus, the elevations in concentrations of sites accurately reflects B max values. While we did not examine D 2 mRNA levels in this study, previous studies have demonstrated that the increase in D 2 receptor number does not always lead to an elevation in D 2 mRNA (Creese et al, 1992;Fox et al, 1994;Matsunaga et al, 1991), although higher doses and more prolonged exposure does elevate D 2 mRNA (D' Souza et al, 1997;Damask et al, 1996;Egan et al, 1994;Lévesque et al, 1995;Rogue et al, 1991). It is likely that a change in posttranslational processing of D 2 receptors also contributes to elevated numbers (Pich et al, 1987).…”
Section: Discussionmentioning
confidence: 81%
“…The concentration of [ 3 H]-spiperone used in this study is approximately 7 times the K d for the D 2 receptor and, thus, the elevations in concentrations of sites accurately reflects B max values. While we did not examine D 2 mRNA levels in this study, previous studies have demonstrated that the increase in D 2 receptor number does not always lead to an elevation in D 2 mRNA (Creese et al, 1992;Fox et al, 1994;Matsunaga et al, 1991), although higher doses and more prolonged exposure does elevate D 2 mRNA (D' Souza et al, 1997;Damask et al, 1996;Egan et al, 1994;Lévesque et al, 1995;Rogue et al, 1991). It is likely that a change in posttranslational processing of D 2 receptors also contributes to elevated numbers (Pich et al, 1987).…”
Section: Discussionmentioning
confidence: 81%
“…In rat pituitary, 21 days of haloperidol upregulated D2 mRNA expression [24]. Although early striatal studies were negative in rodents [2527], subsequent studies found upregulated striatal D2 mRNA expression changes after chronic haloperidol treatment [23, 2832]. Four-week administration upregulated striatal and prefrontal cortical Drd2 expression in rats [22, 32].…”
Section: Resultsmentioning
confidence: 99%
“…Dopamine D 2 receptor mRNA upregulation has previously been reported to be changed by chronic haloperidol treatment, although reports are mixed. 18,19,31 The lack of dopamine D 2 receptor mRNA may suggest that high and sustained levels of D 2 receptor blockade may not have been achieved but high levels of drug in plasma, increased levels of Nts mRNA and high vacuous chewing movement scores in the haloperidol group are indicators of high and sustained D 2 receptor blockade. We did not find any change in Pde10a, Pde1b or D 2 receptor mRNA levels in the striatum after chronic haloperidol treatment; however, we observed a highly significant increase in the striatal Nts mRNA levels indicating transcriptional activation due to antipsychotic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…mRNA levels of four target genes ( Pde10a , Pde1b , dopamine D 2 receptor and neurotensin ) were chosen as changes in expression of these genes due to chronic antipsychotic treatment have been reported. 7,18,19 Western blotting was carried out to quantify striatal protein levels. Total and PDE10A-specific cAMP PDE activity in striatum were measured in enzymatic assays to assess potential changes in PDE activity of PDE10A or other PDEs.…”
Section: Introductionmentioning
confidence: 99%